DESIGN AND PERFORMANCE IMPROVEMENT OF CNTFET BASED CONTENT ADDRESSABLE MEMORY (CAM) CELLS - Hajare, Raju; C.P, Mallikarjunagowda; Deekshitha, Deekshitha; J, Madhuri.; Anaya, Anaya (Institute of Advanced Engineering and Science, 2020)
The scaling down of transistors is of paramount importance to make ICs and devices more portable and efficient. As it is the most basic component of every electronic device, there is need of finding better and innovative methods of transistor characterization. CNTFET has shown the promise and is best suited for today?s faster digital processing units and Memory devices. Here Carbon Nano Tube (CNT) is characterized for its electrical property and then designed a XOR based CAM cell using CNTFET. Both delay and power analysis for the designed CAM is done.